RESILIENCE IN CULTURAL ATTRACTION: A STUDY AT SOMBA OPU FORT, GOWA REGENCY - Helena Widjaja; Ilham Junaid (Politeknik Pariwisata Makassar, 2025)
This paper breaks down what resilience really means and how it helps the destination bounce back from tough times. The research aims to identify the challenges and opportunities in managing cultural tourism at Fort Somba Opu, and to propose strategies for managing Fort Somba Opu from a resilience perspective. This research applies a qualitative method, with the study location being Fort Somba Opu, Gowa Regency, during the period of August-October 2025. The research results indicate that Fort Somba Opu faces various challenges, both between the managers and the community and between the managers and relevant government agencies. These challenges include limited basic and supporting tourism facilities, land use conflicts between the fort area and the local community due to the area's location being mixed with the community, a lack of income sources, and damaged traditional houses. Besides these challenges, Fort Somba Opu also has opportunities that allow it to develop further and survive in the long term, such as being a center for cultural festivals and activities related to culture, and having great potential for collaboration with the private sector to obtain development and expansion funds. The proposed strategy involves short, medium, and long-term approaches, allowing the destination to develop gradually by building a strong foundation at each stage before moving to the next level. The strategy includes: infrastructure improvements (accessibility and providing access for public transportation like busses to enter the fort area), adding facilities such as a Tourist Information Center, souvenir shops, more decent sanitation facilities, and a better lighting system, collaborating with the private sector to obtain development capital, developing innovative tourism packages, and government support by creating policies to separate the tourism area from public road access for the community. The above strategies are part of the Sombu Opu Fort's resilience perspective, applying the concept of resilience and requiring revitalization efforts to revive the fort tourism area amidst external challenges and changes. This research reinforces the urgency of resilience in cultural attractions to protect historical sites from significant threats. This research is expected to make a significant contribution to the development of an applicable resilience concept for the preservation and development of cultural destinations in Indonesia.